Data from: Ecological and biogeographic drivers of biodiversity cannot be resolved using clade age-richness data - Rabosky, Daniel; Benson, Roger (Dryad, 2021)
Estimates of evolutionary diversification rates – speciation and
extinction – have been used extensively to explain global biodiversity
patterns. Many studies have analysed diversification rates derived from
just two pieces of information: a clade's age and its extant species
richness. This "age-richness rate" (ARR) estimator provides a
convenient shortcut for comparative studies, but makes strong assumptions
about the dynamics of species richness through time. We demonstrate that
use of the ARR estimator in comparative studies is problematic on both
theoretical and empirical grounds. We prove mathematically that ARR
estimates are non-identifiable: there is no information in the data for a
single clade that can distinguish a process with positive net
diversification from one where net diversification is zero. Using
palaeontological time series, we demonstrate that the ARR estimator has no
predictive ability for real datasets. These pathologies arise because the
ARR inference procedure yields "point estimates" that have been
computed under a saturated statistical model with zero degrees of freedom.
Although ARR estimates remain useful in some contexts, they should be
avoided for comparative studies of diversification and species richness.